Pengembangan Prekultur Oxgall sebagai Sampel Klinis untuk Deteksi Salmonella typhi dengan Metode Real-time PCR - Gunawan, Annisa Pratiwi; Djuminar, Ai; Ernawati, Ernawati; Chaidir, Lidya (POLTEKKES KEMENKES YOGYAKARTA, 2018)
Typhoid fever is a significant public health burden in low-income countries caused by Salmonella enterica serotype typhi (S.typhi). Clinical manifestations of typhoid fever are varied and non-specific, making the diagnosis difficult. Using oxgall for pre-incubation as a selective culture medium before amplification of Real-time PCR (RT-PCR) in wholeblood produces a fast and sensitive diagnostic. The purpose of this study was to know the performance oxgall-precultured Real-time PCR for detection of Salmonella sp.. Prior to the sample process, spike method optimization was performed to find out that the reagents were well used for clinical specimens. In the sample process, blood samples from 30 Widal-positive patients were collected for this study . Venous blood samples from typhoid fever patients were taken on the day of diagnosis; 5 ml for blood culture, and 5 ml for RT-PCR. The bacteria were grown in oxgall 10% (standard microbiological laboratory clinics) and incubated for 6 hours (37Â° C) before bacterial DNA was isolated for RT-PCR detection. The results showed that reagen of RT-PCR is good used for a clinical sample and a blood culture was better than RT-PCR using oxgall (positive blood culture results over 24 hours). This suggests that there is a need for further research on the duration of incubation and oxgall concentrations in RT-PCR and the selection of clinical samples.